(untitled) (Scientific journal of the Fergana State University, 2024)
The elemental composition of a rock mineral sample was studied in detail for the first time using inductively coupled plasma mass spectrometry (ICP-MS) using an AT 7500 instrument (ICP-MS). In the elemental composition of the rock mineral sample, 61 elements were quantified. As the mass of an element increases, there is a natural tendency for its quantity to decrease.